Educational Policies in Pakistan, Afghanistan, and Tajikistan : Contested Terrain in the Twenty-First Century. - Aksakolov, Sultonbek (Lexington Books, 2016)
This book analyzes the successes and impediments of various educational policies in Pakistan, Tajikistan, and Afghanistan. The authors analyze how current and past discourses on gender, religion, culture, politics, and the economy affect formal education and communal transformation in mountainous regions.